2018
DOI: 10.1016/j.idm.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for HIV prevention study in southwestern areas of China

Abstract: BackgroundChina has ambitious to achieve significant reductions in HIV transmission and HIV-related mortality by adopting the World Health Organization's “Treat All” approach. Such a prevention strategy is needed future study on regional scale.MethodsAn observational cohort study of HIV epidemiology and treatment databases was used to study the effectiveness of antiretroviral therapy on the transmission of HIV in serodiscordant couples in Guangxi of China.ResultsA total of 7713 couples were entered into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…By the end of 2017, 70.2% of the people living with HIV knew their HIV status, 76.8% of the people who knew their HIV-positive status were receiving treatment, and 96.8% of the people receiving treatment had suppressed viral loads in Guangxi [96]. An observational cohort study of HIV epidemiology and treatment databases among serodiscordant couples in Guangxi showed that HIV seroincidence rate was significantly higher among the treatment-naive group (4.2 per 100 person-years, 3.7-4.8) compared with the treatment group (1.6 per 100 person-years, 1.3-1.8) [97]. This corresponded to an overall 45% reduction in risk of HIV transmission among serodiscordant couples who were on ART treatment.…”
Section: Hiv Treatment and Preventionmentioning
confidence: 99%
“…By the end of 2017, 70.2% of the people living with HIV knew their HIV status, 76.8% of the people who knew their HIV-positive status were receiving treatment, and 96.8% of the people receiving treatment had suppressed viral loads in Guangxi [96]. An observational cohort study of HIV epidemiology and treatment databases among serodiscordant couples in Guangxi showed that HIV seroincidence rate was significantly higher among the treatment-naive group (4.2 per 100 person-years, 3.7-4.8) compared with the treatment group (1.6 per 100 person-years, 1.3-1.8) [97]. This corresponded to an overall 45% reduction in risk of HIV transmission among serodiscordant couples who were on ART treatment.…”
Section: Hiv Treatment and Preventionmentioning
confidence: 99%
“…This study was limited as it concentrated on a city in southwestern China, only patients from Liuzhou were included in this study, so the generalizability to other healthcare settings and regions may be limited. Nevertheless, the southwestern region of China contains the most significant number of new HIV infections 32 . Thus this study may be relevant to a substantial part of the current HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Of these potentially relevant articles, 72 publications were excluded for various reasons, while 15 studies met the inclusion criteria and were included in this report. 13,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] These comprised 1 overview of SRs and/or MAs, 18 and 14 nonrandomized studies. 13,14,[19][20][21][22][23][24][25][26][27][28][29][30] Appendix 1 presents the PRISMA 31 flow chart of the study selection.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…13,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] These comprised 1 overview of SRs and/or MAs, 18 and 14 nonrandomized studies. 13,14,[19][20][21][22][23][24][25][26][27][28][29][30] Appendix 1 presents the PRISMA 31 flow chart of the study selection.…”
Section: Quantity Of Research Availablementioning
confidence: 99%